Chromato-mass spectroscopy of tinctures from the underground part of Valerian plants growing in Zaporizhzhia region - V. M. Odyntsova; Yu. I. Korniievskyi; D. Yu. Skoryna; V. Н. Korniievska (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2022)
Modern sedatives used in medical practice can be of both synthetic and natural origin. It is known that the best phytosedative is valerian. In the 18th century, valerian was included in all European pharmacopeias. High efficiency, good tolerability, and virtually no side effects ensure the widespread use of valerian and its phytopreparations in medical practice, especially for the treatment of geriatric patients. Despite this, valerian remains understudied due to its extreme polymorphism.